PSM UMPSA won GOLD Medal at ITEX 24 - Roslinazairimah, Zakaria (Pusat Sains Matematik (PSM), 2024)
Kuala Lumpur, May 17, 2024 – Associate Professor Dr. Roslinazairimah Zakaria, alongside team members Mr. Syahrizal Salleh, Dr. Siti Roslindar Yaziz, and co-inventor Dr. Noor Fadhilah Ahmad Radi from UiTM, garnered a prestigious gold medal at The 35th International Invention, Innovation, Technology Competition & Exhibition Malaysia (ITEX’24).